2011
DOI: 10.1080/15536548.2011.10855904
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Relationships between Selected Contextual Factors and Information Security Concerns in Global Financial Services Institutions

Abstract: This paper examines the relationships between three contextual factors i.e. transparency levels, information and communication technologies (ICT) use laws, and national legal systems efficiency and information security concerns in the global financial services institutions (GFSI). This research essentially seeks to expand the breadth of knowledge provided in the 2009 Deloitte Touche Tohmatsu (DTT) survey, which reported on information security issues in GFSI. This current study used secondaly data sources for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…First, we modified the organizational environment dimension, which focused on the inherent industry risk, to a broader organizational risk environment encompassing the full risk landscape for an organization that uses social media. In doing so, we stress the need for an accurate risk assessment that moves beyond those inherent to an industry and includes: risks from insiders (Ifinedo 2011), employee use of social media, industry risks (Kankanhalli et al 2003) such as legal or regulatory issues that arise from the use of social media, and other nontechnical risks (Spears and Barki 2010). Second, we modify the individual differences dimension to more accurately depict the risk assessment and planning process that organizations utilize when adopting a new technology.…”
Section: Introductionmentioning
confidence: 98%
“…First, we modified the organizational environment dimension, which focused on the inherent industry risk, to a broader organizational risk environment encompassing the full risk landscape for an organization that uses social media. In doing so, we stress the need for an accurate risk assessment that moves beyond those inherent to an industry and includes: risks from insiders (Ifinedo 2011), employee use of social media, industry risks (Kankanhalli et al 2003) such as legal or regulatory issues that arise from the use of social media, and other nontechnical risks (Spears and Barki 2010). Second, we modify the individual differences dimension to more accurately depict the risk assessment and planning process that organizations utilize when adopting a new technology.…”
Section: Introductionmentioning
confidence: 98%
“…For illustration purposes, the socioeconomic factors considered herein are national wealth (GDP), transparency levels (COPT) and country literacy rates (EDUC). Previous IS security-related studies that considered such factors found them to the pertinent to the discourse [12][13][14][15][16].…”
Section: B Socio-economic and Cultural Factorsmentioning
confidence: 99%
“…For the economic variable, we used gross domestic product (GDP) per capita, which refers to a country's gross domestic product divided by its population; it is generally considered an indicator of a country's standard of living or wealth and often used as a differentiator in prior research [10,11,14]. Literacy rates refer to the percentage of people in a country that are literate, that is, able to read and write.…”
Section: B Socio-economic and Cultural Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current organizations depend on information systems (IS) for their existence; this is because such systems often hold treasured organizational data resources (Cavusoglu et al, 2004;Richardson, 2011;Ifinedo, 2009Ifinedo, , 2011Ifinedo, , 2012. To protect the main IS assets held in such systems from misuse, abuse and destruction; organizations often utilize a variety of methods such as installing firewalls, updating anti-virus software, backing up their systems, maintaining and restricting access controls, using encryption keys, using surge protectors, and using wide-ranging monitoring systems (Ryan, 2004;Workman, Bommer and Straub, 2008;Lee and Larsen, 2009).…”
Section: Introductionmentioning
confidence: 99%